Effect of Relative Humidity on the Development of Head Blight by Bipolaris sorokiniana in Wheat - Uddin, Sheikh Afsar; Khalequzzaman, KM; Rashid, AQM Bazlur (Journal of Agriculture & Rural Development, 2008)
Effect of exposure to different duration of high humidity (5,10,15,20,25 & 30 days) on the development of head blight caused by Bipolaris sorokiniana in wheat was studied in vitro. Maximum leaf blight severity of 42.97% and head blight development of 87.53% caused by the pathogen were recorded for the infected plants incubated for a period of 30 days under condition of high humidity. The treatments did not differ significantly with respect to head blight development except the control. Variable effects of the treatments was observed on the grain quality. The highest diseased (black pointed and shriveled) grains of 62.27% were recorded in treatment 6 (30 days exposure) followed by treatment 5 (25 days exposure) with 48.01% diseased grains. There were no significant differences among the other treatments except the check.Key words: Humidity, head blight, leaf blight, Bipolaris sorokiniana, wheat.